2006
DOI: 10.1007/s11182-006-0240-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure analysis of electrically conductive polymers filled with agglomerated components

Abstract: An analysis of macrostructure topology of electrically conductive polymer composites with agglomerated fillers is performed. Parameters that allow the value of volume electrostatic resistance and agglomeration of the filler are determined.Structurally heterogeneous (multi-component) materials possess unique consumer properties due to a virtually infinite ability of varying their characteristics. An efficient application of these materials largely depends on an understanding of the fundamentals of their propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In [12] it was shown that for the constant step ε of the squared mesh covering photomicrographs of the structure of different materials, the plots of dependence p i on ln ε are well described by a linear dependence (here p i is the probability to find a fractal point in the ith mesh). The slope angle of the straight line yields information of dimension D 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In [12] it was shown that for the constant step ε of the squared mesh covering photomicrographs of the structure of different materials, the plots of dependence p i on ln ε are well described by a linear dependence (here p i is the probability to find a fractal point in the ith mesh). The slope angle of the straight line yields information of dimension D 1 .…”
Section: Resultsmentioning
confidence: 99%
“…According to [10], the structural parameter D 1b responds to the agglomeration-deagglomeration processes of the filler in the electroconductive grid and hence, to the degree of grid branching. This parameter is determined from an analysis of the texture of photomicrographs of the material structure.…”
Section: Main Results Of Invtstigationmentioning
confidence: 99%
“…The parameter works by means of a comparison of photomicrographs of the material with the known properties with those of the material being synthesized. The filler-polymer boundaries are identified from gradations of grey color in the photomicrographs using a specially adjusted texture parameter that allowed the boundaries with minor changes in the grey color to be taken into account [10]. The texture parameter characterizing the autocorrelation of the histogram of joint distribution of the second-order brightness, namely, the interrelation between two neighboring points in photomicrographs turned out to be efficient.…”
Section: Main Results Of Invtstigationmentioning
confidence: 99%
“…A quantitative description of interphase boundary contours were thus performed using the Renyi fractal dimensions. Then, the fraction numerator dependence plot was made according to formula (1) along the denominator (mesh size) [7,8]:…”
Section: Methodsmentioning
confidence: 99%
“…It is designated by D 1b . In [7] it was shown that this parameter reflects the character of electroconductive mesh formed during the technological process.…”
Section: Methodsmentioning
confidence: 99%